Enforcing IPRs Through Investor‐State Dispute Settlement: A Paradigm Shift in Global IP Practice. (March 2016) - Upreti, Pratyush Nath
Abstract : Globally, we are moving towards stronger Intellectual Property Rights. Intellectual Property Rights (IPRs) have become an integral part of the regulatory system and they are included in investment, regulations and trade policies. It is now important to understand the linkage between them. Recent practices of International Investment Agreements (IIAs) include intellectual property as a definition of investment, giving the investor an alternate forum to enforce their IP under International arbitration tribunal. International investment laws focus mostly on the rights of the investor and diverse opinions of generally accepted international principles such as fair and equitable treatment that encourage investors to litigate intellectual property through Investor State Dispute Settlement (ISDS). This article will focus on the relationship between intellectual property and investment agreement in three aspects. The first part of the article will focus on how intellectual property is treated as an investment. The second part emphasizes how an investor uses an investment agreement as a tool to enforce intellectual property. The last part of the article highlights the possible impacts of litigating intellectual property under ISDS, particularly focusing on TRIPS flexibility.